An Avian Sarcoma/Leukosis Virus-Based Gene Trap Vector for Mammalian Cells - Zheng, Xiangqun H. (American Society for Microbiology, 1999)
RCASBP-M2C is a retroviral vector derived from an avian sarcoma/leukosis virus which has been modified so that it uses the envelope gene from an amphotropic murine leukemia virus (E. V. Barsov and S. H. Hughes, J. Virol. 70:3922–3929, 1996). The vector replicates efficiently in avian cells and infects, but does not replicate in, mammalian cells. This makes the vector useful for gene delivery, mutagenesis, and other applications in mammalian systems. Here we describe the development of a derivative of RCASBP-M2C, pGT-GFP, that can be used in gene trap experiments in mammalian cells. The gene trap vector pGT-GFP contains a green fluorescent protein (GFP) reporter gene. Appropriate insertion of the vector into genes causes GFP expression; this facilitates the rapid enrichment and cloning of the trapped cells and provides an opportunity to select subpopulations of trapped cells based on the subcellular localization of GFP. With this vector, we have generated about 90 gene-trapped lines using D17 and NIH 3T3 cells. Five trapped NIH 3T3 lines were selected based on the distribution of GFP in cells. The cellular genes disrupted by viral integration have been identified in four of these lines by using a 5′ rapid amplification of cDNA ends protocol.